(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper analyzed the Belt Road Initiative (BRI) by China and how this has transformed the connectivity of the countries in the Indo-Pacific region with special regard to the involvement of Pakistan under the China-Pakistan Economic Corridor (CPEC). Using mixed-methods approach, the research conducted primary analysis utilizing semi-structured interviews of government officials and representatives of Chinese enterprises in addition to business leaders, and employing survey method to gather structured data in major cities of Pakistan. The secondary type of data was received through government improvised facts, global reports, as well as statistical frames. The study found that BRI has made great improvements in the infrastructure connectivity in Pakistan especially with regard to the above three sectors transportation, energy and telecommunications. Among the main findings, it was noted that CPEC projects enhanced the region trade routes, energy security, and the region economic integration, as a part of the Indo-Pacific system. Nonetheless, the research also indicated such issues as the problem of debt sustainability, environmental issues, and geopolitical conflicts. The analysis revealed that although there were significant opportunities that BRI presented with regard to regional connectivity, proper policy coordination and sustainable means of financing projects was very important to help countries involved to achieve maximum benefits and reduce risks that the initiative poses.